2018
DOI: 10.3390/nu10101405
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome and Radiation Induced-Bowel Injury: Evidence for Potential Mechanistic Role in Disease Pathogenesis

Abstract: Radiotherapy has played a major role in both the curative and palliative treatment of cancer patients for decades. However, its toxic effect to the surrounding normal healthy tissue remains a major drawback. In cases of intra-abdominal and/or pelvic malignancy, healthy bowel is inevitably included in the radiation field, causing undesirable consequences that subsequently manifest as radiation-induced bowel injury, which is associated with significant morbidity and mortality. The pathophysiology of radiation-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
110
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 99 publications
2
110
0
Order By: Relevance
“…However, its toxic effect to the surrounding normal healthy tissue remains a major drawback. Evidence has shown that the widespread use of ionizing radiation (IR) can cause high incidence of radiation-induced side effects in up to 75% during the process of radiotherapy [ 2 ]. The most common IR exposure damage effects are bone marrow inhibition and gastrointestinal toxicity [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, its toxic effect to the surrounding normal healthy tissue remains a major drawback. Evidence has shown that the widespread use of ionizing radiation (IR) can cause high incidence of radiation-induced side effects in up to 75% during the process of radiotherapy [ 2 ]. The most common IR exposure damage effects are bone marrow inhibition and gastrointestinal toxicity [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment for almost all types of cancers includes surgery, chemotherapy, and radiation. Ionizing radiation results in the damage of DNA, which ultimately results in cell death [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although ionizing radiation is highly effective at inducing DNA damage in cancer cells, which leads to cell death, nearby healthy cells are also affected [2]. Localized radiation is possible with most cancers, but for abdominal cancers a broader eld area of ionizing radiation is necessary and can cause serious effects on normal tissue including the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations